The Asymmetry of the Magnetic Field Distribution in a Flat Unshielded 3-phase High Current Busduct - Kusiak, D.; Piątek, Z.; Szczegielniak, T. (Acta Technica Jaurinensis, 2013)
It has been demonstrated in the paper that the magnetic field distribution in two outer conductors of the flat, three-phase, high-current busduct is asymmetric. The components of this field reflect the magnetic field of the reverse reaction fields of the eddy currents induced in the conductors of the adjacent phases as the results of the proximity effect and the skin effect. The field distribution is shown in the outer area of the outer phases as the function of the parameters reflecting the current frequency, the conductivity, and the transverse dimensions of the tubular conductors. The results also account for the fact that analogously in the high-current busducts of this type the active power losses, temperature distributions, and electrodynamic forces, will not be the same in the outer buses.